Analisis Pengelolaan Logistik Farmasi di Instalasi Farmasi RSUD Raden Mattaher Selama Pandemi Covid-19 - Muhammad Ihsan Pratama; Muhammad Syamsu Hidayat; Rochana Ruliyandari (Syntax Literate, 2023)
The efficiency of the pharmaceutical logistics management process can indirectly affect the balance of pharmaceutical supplies in hospitals. The aim of this research is to analyze the management of pharmaceutical logistics at Raden Mattaher Regional Hospital, Jambi Province during the Covid-19 pandemic. The method used in this research is descriptive qualitative using a phenomenological approach. The variables looked at include selection, planning, budgeting, procurement, storage and distribution. Data collection in this research was carried out by means of observation, in-depth interviews, and data review. The research results show that the guidelines in the Raden Mattaher Regional General Hospital Pharmacy Installation, Jambi Province are in accordance with the regulations issued by the Ministry of Health, however, in implementation there are still several things that have not been implemented and need to be evaluated regularly in accordance with the hospital's needs and Avoid things that are beyond predictions that are detrimental in the future.